The antimicrobial effects of Citrus limonum and Citrus aurantium essential oils on multi-species biofilms - Sarah Almeida Coelho Oliveira; Jéssica Rabelo Mina Zambrana; Fernanda Bispo Reis Di Iorio; Cristiane Aparecida Pereira; Antonio Olavo Cardoso Jorge (Sociedade Brasileira de Pesquisa Odontológica, 2014)
The aim of this study was to evaluate the effects of Citrus limonum and Citrus aurantium essential oils (EOs) compared to 0.2% chlorhexidine (CHX) and 1% sodium hypochlorite (NaOCl) on multi-species biofilms formed by Candida albicans, Enterococcus faecalis and Escherichia coli. The biofilms were grown in acrylic disks immersed in broth, inoculated with microbial suspension (106 cells/mL) and incubated at 37°C / 48 h. After the biofilms were formed, they were exposed for 5 minutes to the solutions (n = 10): C. aurantium EO, C. limonum EO, 0.2% CHX, 1% NaOCl or sterile saline solution [0.9% sodium chloride (NaCl)]. Next, the discs were placed in sterile 0.9% NaCl and sonicated to disperse the biofilms. Tenfold serial dilutions were performed and the aliquots were seeded onto selective agar and incubated at 37°C / 48 h. Next, the number of colony-forming units per milliliter was counted and analyzed statistically (Tukey test, p ≤ 0.05). C. aurantium EO and NaOCl inhibited the growth of all microorganisms in multi-species biofilms. C. limonum EO promoted a 100% reduction of C. albicans and E. coli, and 49.3% of E. faecalis. CHX was less effective against C. albicans and E. coli, yielding a reduction of 68.8% and 86.7%, respectively. However, the reduction of E. faecalis using CHX (81.7%) was greater than that obtained using C. limonum EO. Both Citrus limonum and Citrus aurantium EOs are effective in controlling multi-species biofilms; the microbial reductions achieved by EOs were not only similar to those of NaOCl, but even higher than those achieved by CHX, in some cases.